External change management: the revised policy of registered construction health and safety agents in South Africa - Khoza, Sepelong Rebecca (My University, 2021)
Purpose: South Africa’s construction industry continuously strives to improve its health and safety( H&S). Consequently, South Africa revised its Construction Regulations in 2014 to include the requirement for the application for construction permit to include a competent construction health and safety (CHS) agent. This research investigates how change management processes enable construction companies to effectively comply with the revised H&S policy requirement. Design/methodology/approach: Using a cross-sectional survey design, an online structured questionnaire was sent to SACPCMP-registered construction professionals and construction professionals of a state-owned enterprise in South Africa using purposive sampling. 170 construction professionals responded (85% response rate). Likert scale/ ordinal data were collected on the factors affecting the registration for the CHS agents (Objective 1), understanding of the implications of implementing the revised H&S policy (Objective 2), applicability of the different change management strategies (Objective 3), and the attitudes towards organizational changes for implementing the revised H&S policy (Objective 4). Findings: There was a strong agreement that H&S is best implemented in the early phases of construction project (Objective 1). Average understanding existed that any person who is interested in being an H&S agent can become one by going for an interview only(Objective 2). Also, there was a strong agreement that project participants’ need to comply with the changes as required by the law (Objective 3) and that the attitude of top management towards change is positive (Objective 4).Research limitations/implications: The construction professionals acknowledge that the revised H&S policy needs to be adhered to, as per the law, however there are hindrances to being registered because of factors that can be sorted out by management and how they roll out the change management within the companies. Originality/ Value: The Ingenuity of the research is based on the change management in the context of the revised H&S policy in South Africa
A research report submitted in partial fulfilment of the degree of Masters in Construction Project Management (MSc) in the field of Built Environment, School of Construction Economics and Management, University of the Witwatersrand, 2021